EFFECTIVENESS OF PAYMENT FOR FOREST ENVIRONMENTAL SERVICES (PFES) TOWARD SUSTAINABLE FOREST MANAGEMENT IN DA BAC DISTRICT, HOA BINH PROVINCE - Van Truong, Vu; Thi Bich Hao, Nguyen; Phu Tuan, Le; Van Kha, Pham; Thi Huong, Tran; Duy Quang, Pham (Journal of Forestry Science and Technology, 2022)
By conducting interviews, summarizing and analyzing secondary documents, and employing a set of published indicators to evaluate the payment for forest environmental services (PFES), the research has examined the current status of the forest in the study area as well as the contribution of special-use and protection forests to revenue improvement from PFES. The results show that PFES in Da Bac district has high transparency, fairness and effectiveness. However, the results of the SWOT analysis demonstrate that the current situation of PFES and forest protection and development in Da Bac have been facing many difficulties and challenges, such as poor coordination among stakeholders in implementing PFES; forest protection and development with low effectiveness and consolidation; lack of forest rangers according to the provisions of law; pressure caused by natural forest exploitation activities of people living in neighboring communes outside the basin; and regularly updated technology requiring forest rangers and staff from the forest protection and development fund to quickly perceive it in order to successfully complete their tasks. Therefore, solutions have been proposed to improve the effectiveness of PFES towards sustainable forest development.